Quality Assurance of Drug Information Service and Drug Therapy Review Provided by Clinical Pharmacists in an Indian Teaching Hospital - Patel, Himanshu; Churi, Shobha; Gurumurthy, Parthasarathi; Madhan, Ramesh (Indian Journal of Pharmacy Practice)
Background: To ensure the competent delivery of patient care by clinical pharmacists, it is essential to evaluate services provided by them. Objectives: This study was conducted to assess the impact of Standard operating procedure (SOP) on quality of Drug information (DI) service and drug therapy review provided by clinical pharmacy department. Methods: The study was conducted at department of clinical pharmacy located at tertiary care teaching hospital. Quality assessment checklist was designed to assess the quality of both services. Based on score obtained from checklist each service was graded at different levels. Quality of services provided was compared before and after implementation of SOP. Also questionnaire was circulated among health care professionals of various medical departments to evaluate their perception and opinion about mentioned services provided. Results: Before implementation of SOP, out of 70 DI evaluated, 35.7% of them were found to be excellent, 41.4% of them were found to be good, whereas it was found that 22.9% of DI needed improvement. After implementation of SOP, out of 85 DI evaluated, 82.4% of DI provided was found to be excellent and remaining DI provided (17.6%) was found to be good. Before implementation of SOP, out of 64 interventions provided, 65.6% of them were found to be excellent and 26.6% of them were found to be good, however, 7.8% of them needed improvement. After implementation of SOP, 64 interventions were evaluated and out of which 87.5% of them were found to be excellent and 7.8% of them were found to be good. However, only 4.7% of them needed improvement. Majority of medical staff (77%) felt that clinical pharmacists actively contribute in drug therapy decision making and overall performance of clinical pharmacist was rated as “Good” by medical staff. Conclusion: The quality of both, DI service and drug therapy review was found to be improved after implementation of SOPs. Also, quality of both services provided is an important factor influencing the acceptability of clinical pharmacist’s contributions.
Keywords: Quality assurance; Clinical Pharmacy Services; Drug Information; Drug therapy review; Pharmacy Practice